Analysis Design And Development Of Sales Promotion At Astakona Anugerah Abadi Using Extreme Programming Method - Calvin Pang; Muhammad Ardiansyah (Universitas Internasional Batam, 2023)
This technology is used in various fields that apply information technology, everyone can easily and quickly get new information. Using this technology as a tool that can process data so that product requests ordered by customers can be processed immediately without stock, and if the product is not available then Product Requests will be processed to the production department. Jobs related to information technology, the development of information technology is currently growing so rapidly, starting from industry, education, banking, shops, internet cafes and even households. In designing and developing PT. Astakona Anugerah Abadi the author uses the Extreme Programming (XP) method to facilitate design by dividing into four stages in the form of planning, design, coding and testing each of which is described in the results and discussion. The results of this study are in the form of conclusions and feedback from clients which are then set forth in the form of research.